Supporting the Ethical Use of Artificial Intelligence Applications in Universities - A Research Based on Students Opinions - Anca Draghici; Caius Luminosu; Angela Repanovici; Manolis Koukourakis; Valerij Dermol; Ilie Mihai Taucean (International School for Social and Business Studies, 2024)
Purpose: The purpose of the research was to identify a feasible way to support the ethical use of AI in universities based on identifying how the AI software application ChatGPT is used in education at higher education institutions and with students in different majors. Study design/methodology/approach: The research methodology consisted of the following stages: (1) a survey based on a questionnaire designed considering the Technology Acceptance Model (TAM) framework to collect students' opinions on the use of AI ChatGPT; (2) The results of the survey were used to design the materials of the AI Transmedia Campaign, but also to identify the best distribution channels of them; (3) After implementing the AI Transmedia Campaign, a feedback survey was developed, ascertaining the effectiveness of the approach to create an ethical behaviour towards the AI software application in general, and on AI ChatGPT, in particular. Findings: Research shows a gap in regulating the ethical use of AI applications in higher education. Thus, the AI Transmedia Campaign has been well received and appreciated by all categories of students. Originality/value: The research is international and was carried out in higher education institutions in Romania, Greece, and Slovenia (the size of the research sample, 2942, proves the scope of the study). The research results have demonstrated and characterised the students' behaviour (the cognitive response and the intention to use) towards the use of AI ChatGPT and the utility of the AI Transmedia Campaign realised in the context of the implementation of the RespectNET project (2021-1-IT02-KA220-HED-000027578, https://respectnet.eu/).